Determination of the oxalate content in food and the influence of this ion on the human organism (Research, Society and Development, 2021)
It is known that foods are essential for the proper functioning of the body as they present the nutrients necessary for homeostasis. However, foods also have antinutrients, such as calcium oxalate, which can damage the urinary system, such as the formation of kidney stones. In this approach, this study aimed to review the literature on the renal system, the influence of oxalate on the human body and also determine the concentration of oxalate present in tomato, sweet potato and eggplant extracts. For bibliographical research, articles were searched using databases such as Google Scholar, Scielo, Bireme and ScienceDirect, with the following descriptors in Portuguese: calcium oxalate, kidney diseases, oxalate determination in food and later, the same descriptors were searched in English. For the determination of oxalate, tomato, eggplant and sweet potato extracts were prepared, and then the extracts were analyzed by the permanganimetry method. The results showed that there is a relationship between the formation of kidney stones with the consumption of foods that contain oxalate, and it is possible to conclude that the inadequate intake of water associated with a diet rich in foods that contain oxalate, can contribute to the formation of kidney stones. Thus, it is very important to monitor these patients by a nutritionist, in order to provide guidance on the restriction of consumption of these foods and advice on the importance of ingesting an adequate volume of water.